National Defense College of the Philippines Library collection evaluation through collection mapping and conspectus approach - De Castro, Rachel Ann D.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
The National Defense College of the Philippines (NDCP) is the highest educational institution in the country dedicated to the conduct of advanced programs in national security administration. Its library is comprised with 3138 volumes of reference books, magazines, periodicals, research works of students and other studies by the staff, faculty and consultants of the College.
This study aimed to evaluate the book collection of the National Defense College of the Philippines Library. It aimed to know the collection's strength to which it is reflective of the curricular objectives of the college. This study sought to answer the following specific problems: (1) Which areas of the book collection are strong to match the NDCP Curricula? (2) What is the qualitative level of collection support for the academic program of the NDCP? (3) Which areas of the NDCP Curricula can be served most effectively by the book collection? (4) Which parts of the collection are irrelevant?
The descriptive method of research was used for this study. The collection was evaluated through collection mapping and RLG conspectus Approach. RLG Conspectus was used as the evaluation criteria for the study. A table was then used as an evaluation tool to gather the needed information for the study to meet the set objectives.
The study shows that Socio-Cultural Dimension of National Security. National Security Economics 1 and 2, National Security Management 1 and 2, Political Dimensions of National Security (Domestic Environment) and National Security Studies: Contemporary Issues and Problems are the areas of their collection and is strong to meet the NDCP Curricula. The collection constitutes 1826 or 58.18 of materials on instructional support, research and comprehensive level of RLG Conspectus which states that the collection can support the needs of their senior students who are doing their graduate researches.
Two thousand two hundred ninety-one books were found to be relevant to the MNSA courses that mostly fell under Science and Technology related classes (DDC Class numbers 100, 300, 500 and 600). Only twenty-seven percent (eight hundred forty-seven titles) of the total number of titles was not mapped to the courses which mostly fell under religion, Arts, Literature and Rhetoric and Geography and History. This percentage is considered to be irrelevant, at least theoretically, or not directly used by the students of NDCP for their curricular requirements.
Due to the study's findings, some of the recommendations for the improvement of their library were as follows: continue acquiring materials that can better support the graduate courses to continually form a research level and comprehensive collection for them to acquire more materials on the part the collection where it was found to be weak such as: Policy Science and International Systems, Military Dimension of National Security & Foreign Policy (ISAPF).
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: National Defense College of the Philippines Library -- Evaluation